PENGARUH ETIKA PROFESI DAN INDEPENDENSI AUDITOR TERHADAP PENDETEKSIAN FRAUD DENGAN PROFESIONALISME AUDITOR SEBAGAI VARIABEL MODERASI - Raviana Hassan (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2019)
AbstractThe objectives of this research to empirically analyze the influence of Professional Ethics and Independence of Auditors on Detection of Fraud with Auditor Professionalism as a Moderating Variable. The population in this research are auditors who worked on The Public Accountant Firm / Kantor Akuntan Publik (KAP). Sampling was conducted using a conviniance sampling. Primary data collection method used is questionnaire method. The data are analyzed by using Partial Lease Squares (PLS). The results showed that Professional Ethics, Independence and Auditor Professionalism had a positive effect on Fraud Detection. This study also shows that Auditor Professionalism as moderating is not able to strengthen the positive influence of Professional Ethics on Fraud Detection while Auditor Professionalism as moderator can strengthen the positive influence of Auditor Independence on Fraud Detection.